Korelasi Antara Konstitusi dan Kekuasaan dalam Mempertahankan Nilai Nilai Konstitusi - Barly Harly Siregar; Hadist Sulistiawati; Fitria Novita Sari; Mellysa Meha; Naura Fitri Zaskia Sinambela; Putri Rizka Anindya; Ahmad Wahyu Harahap; Tita Nazwa Natalia; Rizka Dina Varissa; Khairil Ramdhan; Fathan Nabil Siregar (Economic Reviews Journal, 2024)
Lack of adequate legal protection for people in Indonesia, social injustice, and social and economic inequality between regions and groups of people, which results in injustice in the distribution of resources and services as well as social welfare, and limited human rights. The research method is descriptive qualitative, which is commonly used in constitutional research including: Literature study, document analysis, conducting discussions with relevant political experts and actors and then conducting content analysis. The results of the brief review, namely the Study of the Constitution in Indonesia, are very important in understanding the legal and political basis of the Indonesian state. Constitutional Studies students must have 21st century skills such as an understanding of basic concepts in the constitution, the ability to analyze issues related to the constitution, the ability to identify weaknesses in constitutional documents and the ability to propose changes needed for the progress of the Indonesian state. In the controversy over choosing to return to the original 1945 Constitution or remain in the 1945 Constitution of the Republic of Indonesia, it is important for us to have a deep understanding of constitutional documents and issues related to them as well as the ability to think critically to consider the arguments of each party. It is important for us to apply and implement the current UUD in accordance with the spirit and principles contained therein for the advancement of the Indonesian state.